Makna Lawang Sekepeng Bagi Masyarakat Dalam Upacara Perkawinan Adat Dayak Ngaju Desa Tumbang Rahuyan Kecamatan Rungan Hulu Kabupaten Gunung Mas - Ameiliani Ameiliani; Anita Pransiska; Evelin Kristiani; Latry Latry; Ahmad Saifulloh (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The issues discussed are the meaning of Lawang Sekepeng, which is a martial art and one of the traditions that exist in Dayak Ngaju traditional weddings. on the Ngaju Dayak wedding tradition. Methods of data collection in this research plan using observation techniques, interviews, recorded information orally. Methods of data analysis carried out open data collection, which is based on general questions, and analysis of information from participants. The results of the research show that it can develop knowledge about the Lawang Sekepeng Ritual and so that this tradition can always be preserved. Lawang Sekepeng rituals have strong traditional and religious values, Lawang Sekepeng attractions at weddings aim to enliven and welcome the arrival of the groom as well as to get rid of all obstacles and misfortunes that can be experienced by prospective husbands and wives in living a married life.